INOVATIVE SYSTEMS OF SEMI-TRAILERS IN CONTINENTAL INTERMODAL TRANSPORT (Perner's Contacts, 2009)
The paper deals with alternative of semi-trailer systems of intermodal transport. This transport vehicles are semi-trailers with extended length and European Modular System (EMS) – eurocombi. The semi-trailers with extended length allow the vehicle to carry 10% more volume than a current semi-trailer. The EuroCombi allows transport volume to be increased by up to 50 percent per vehicle, compared to today’s truck combinations.
Keywords: semi-trailer; intermodal transport; eurocombi; gigaliner